2012
DOI: 10.1021/ac300798g
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Weak and Strong Organic Acids in Atmospheric Aerosols by Capillary Electrophoresis/Mass Spectrometry and Ultra-High-Resolution Fourier Transform Ion Cyclotron Resonance Mass Spectrometry

Abstract: A novel approach using a combination of capillary electrophoresis/mass spectrometry (CE/MS) and off-line Fourier transform ion cyclotron resonance mass spectrometry (FTICR-MS) revealed the structural details of acidic constituents of atmospheric organic aerosol. Both techniques utilized electrospray ionization (ESI), a soft ionization method, to facilitate the analysis of complex mixtures of organic compounds. CE/ESI-MS using an UltraTrol LN-precoated capillary and acidic background electrolytes at different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 54 publications
4
37
0
Order By: Relevance
“…To investigate isotope effects, a comparison of the respective P/R ratio was conducted by spiking fumaric acid and 13 C 4 -fumaric acid into rat plasma. Fumaric acid, after subtraction of the endogenous level, showed an 80% decrease in 1 h, similar to that observed for 13 Table 3). The results suggest that there are no isotope effects while using 13 C 4 -fumaric acid for the stability evaluation (p < 0.01).…”
Section: Product/reactant (P/r) Ratio and Isotope Effects Evaluationsupporting
confidence: 86%
See 2 more Smart Citations
“…To investigate isotope effects, a comparison of the respective P/R ratio was conducted by spiking fumaric acid and 13 C 4 -fumaric acid into rat plasma. Fumaric acid, after subtraction of the endogenous level, showed an 80% decrease in 1 h, similar to that observed for 13 Table 3). The results suggest that there are no isotope effects while using 13 C 4 -fumaric acid for the stability evaluation (p < 0.01).…”
Section: Product/reactant (P/r) Ratio and Isotope Effects Evaluationsupporting
confidence: 86%
“…Furthermore, fumaric acid/fumarate is highly polar, and not retained well on a reversephase column. Other analytical methods for fumarate include GC and CE coupled to MS [12,13]. GC enables the separation and retention of hydrophilic compounds but requires derivatization to improve volatility, therefore complicating sample preparation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One study also reported that HULIS could have a marine source (Cavalli et al, 2004). The molecular composition of HULIS was also studied using ultrahigh resolution mass spectrometer (e.g., Wozniak et al, 2008;Lin et al, 2012a, b;Yassine et al, 2012). Through composition study, it was confirmed that biomass burning and secondary formation process were sources of HULIS (Lin et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…This high degree of chemical complexity of atmospheric organics has inspired a number of sophisticated approaches that are capable of identifying and detecting a variety of different analytes in OA . Among them, ultrahigh‐resolution Fourier transform ion cyclotron mass spectrometry (FTICRMS) involving electrospray ionization has contributed substantially to organic aerosol research . The ultrahigh resolution (over 400 000 at nominal mass of 400) and high mass accuracy (less than 200 ppb) achieved by FTICRMS allow for assignment of a unique elemental composition, and enable the calculation of molecular formulae for these species .…”
mentioning
confidence: 99%